Risk of hearing loss in non-operated ear due to mastoid drilling - Agrawal, Neetu; Sachdeva, Kavita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: The study purpose is to evaluate the effect of drill-generated high intensity noise on hearing sensitivity in contralateral ear. Methods: Sixty patients who underwent mastoidectomy were studied to see the effect of mastoid drilling on hearing sensitivity in normal ear using pure tone audiometry (PTA) and distortion product otoacoustic emission (OAE) values recorded preoperatively and postoperatively. Results: For PTA, there is no significant hearing loss for 0.25 kHz and 0.50 kHz for all PODs. For 1 kHz, 2 kHz and average PTA there is significant temporary hearing loss from POD 1 to POD 7 which normalizes around POD 30. However, there is significant temporary threshold shift for 4 kHz and 8 kHz from POD 1 to POD 5 and the hearing sensitivity improves to preoperative levels at POD 7. For OAE, 1 kHz, 4 kHz and average OAE there is significant temporary hearing loss from POD 1 to POD 7 which normalizes around POD 30. However, there is significant temporary threshold shift for 2 kHz and 6 kHz from POD 1 to POD 5 and hearing sensitivity improves to preoperative levels at POD 7. There is a significant correlation between drilling duration and PTA averages and OAE averages. Conclusions: Sensorineural hearing loss is more prevalent following modified radical and radical mastoidectomy as compared to canal wall up mastoidectomy. The factors influencing postoperative contralateral ear sensorineural hearing loss are type and size of burr and the duration of burr use.